FORMATION AND EVOLUTION OF POLITICAL ELITES: A COMPARATIVE ANALYSIS OF HISTORICAL AND CONTEMPORARY APPROACHES - Роман КОЗАЧЕНКО (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article examines the process of formation and evolution of political elites, as well as changes in their functioning under the conditions of globalization and technological transformations. The aim of the work is to analyze historical approaches to the study of political elites and their evolution in the context of contemporary changes. The research is based on a comparative method that allows identifying the key trends characterizing the functioning of elites in various political systems and social contexts. The relevance of the study is determined by the need to reassess classical approaches to elites, particularly in the context of the influence of global factors such as international organizations, transnational corporations, and the development of information technologies. The problem of democratic legitimacy of political elites in the conditions of postmodernism, especially in post-Soviet countries, where political elites are influenced by both internal and external factors, is highlighted. The main results of the research include the identification of key stages in the development of political elites, as well as new approaches to studying them in the context of technological and social changes. Specifically, the role of information technologies in changing political communication and the influence of new social groups on the formation of political elites are analyzed. New approaches to ensuring the democratic legitimacy of elites through feedback mechanisms between elites and voters are also considered. The practical significance of the work lies in revealing modern trends in the evolution of political elites, allowing for a deeper understanding of their role in democratic processes and political changes. It also opens new perspectives for research in political theory, particularly in the context of globalization, the influence of international institutions, and the impact of new technologies on political structures. The conclusions of the article highlight the importance of reassessing traditional approaches to the study of political elites in the context of contemporary challenges such as globalization, digitalization, and changes in the social structure of society.